Exclusive breastfeeding until six months of age and its influence on anthropometric indices: A prospective observational study - Asha Jyothi Penugonda; Magdalenal Robert; George Ipe Vettiyil; Balamurugan Durai; Rajeev Zachariah Kompithra; Lakshmanan Jeyaseelan; Leni Grace Mathew (Asian Journal of Medical Sciences, 2025)
Background: The WHO recommends exclusive breastfeeding (EBF) for the first 6 months of life, for all infants; and prescribes WHO Multicentre Growth Reference Study charts for growth monitoring. However, real-time differences in growth patterns between EBF and non-EBF infants and its influencing factors have not been well documented and analyzed in India. Aims and Objectives: We conducted a prospective study to assess the prevalence of EBF and the extent of influence of modifiable and nonmodifiable variables on anthropometric indices among infants from birth to 6 months of age. Materials and Methods: Healthy term infants born in a tertiary care hospital in South India were recruited at birth. Sociodemographic data were collected, and diary cards were given to mothers to record daily feeding patterns. Weight, length, and head circumference (HC) were measured using standardized calibrated equipment at birth, 6, 10, 14, and 26 weeks during their routine immunization visits. Data were analyzed and compared for each anthropometric parameter and gain, for each time point and interval, respectively, using SPSS IBM Statistics 22. Generalized estimating equation (GEE) was calculated to assess the independent influence of potential sociodemographic predictors on anthropometric gains. Results: The prevalence of EBF among 450 infants (M: F=1.3:1) who completed the study was 47% at 6 months. The mean duration of EBF was 22.13 weeks (95% CI 18.18–22.57). The GEE analysis showed that the weights, lengths, and HCs of female babies were significantly 392 g, 1.10 cm, and 0.74 cm lesser respectively, compared to male babies across the time period (each P<0.001). Firstborns had significantly lower growth indices than second born infants (each P≤0.02). Furthermore, among infants not given EBF, their weight was significantly 119 g (P=0.02) less compared to those given EBF. Conclusions: Among the significantly influential predictors/parameters, EBF-a modifiable factor, independently influences infant anthropometric parameters positively.